Socialization of Augmented Reality–Based Learning Media for Volcanology Education - Hardian Oktavianto; Dodik Aris Setiawan; Budi Satrio Bakti; Dudi Irawan (Journal Of Humanities Community Empowerment, 2026)
Teaching volcanology in vocational high schools often faces challenges, particularly in explaining abstract concepts and dynamic natural processes. Limited availability of interactive and visual learning media results in suboptimal student understanding of volcanology topics. This community service activity aimed to improve students’ understanding and learning quality through the socialization of Augmented Reality (AR)-based learning media for Phase E volcanology at SMK Muhammadiyah 3 Tegaldlimo, Banyuwangi. The activity employed a participatory approach consisting of preparation, AR media development, teacher training, student socialization and mentoring, as well as evaluation and monitoring stages. Evaluation was conducted by measuring students’ understanding through pre-test and post-test, observing student engagement and learning motivation, and assessing teachers’ ability to integrate AR into classroom instruction. The results indicated a significant improvement in students’ understanding of volcanology concepts after using AR-based learning media. Student engagement and learning motivation also increased, as reflected in higher participation and enthusiasm during learning activities. Furthermore, the training program enhanced teachers’ competence and confidence in integrating AR technology into teaching practices. These findings demonstrate that Augmented Reality is an effective tool for supporting interactive, contextual, and innovative science learning in vocational education